EKSPLORASI SIFAT FUNGSIONAL DAN APLIKASI BAKTERI ASAM LAKTAT PENGHASIL EKSOPOLISAKARIDA PADA PRODUK SUSU FERMENTASI - Putri Dian Wulansari; Novia Rahayu; Nurul Frasiska; Firgian Ardigurnita (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Exopolysaccharides are a class of extracellular biopolymers synthesized by bacteria. Exopolysaccharides are widely used in the dairy industry because of the interest in their health benefits and the improvement in the quality of the products they offer. This article describes the bacterial exopolysaccharide related to factors affecting exopolysaccharide growth, structure and growth of exopolysaccharide strains, exploration of exopolysaccharide strains from various sources, the health benefits they offer, the impact of using exopolysaccharide on product quality, and its application of exopolysaccharide strains in fermented milk products. Exopolysaccharides are claimed to have health-promoting benefits such as: anti-carcinogenic, antioxidant, immunomodulatory and lowering blood cholesterol. In addition, exopolysaccharide strains have the benefit of improving product quality because exopolysaccharides act as thickening, emulsifying and gelling agents. The application of exopolysaccharide strains is widely used in the dairy industry such as in products: yogurt, kefir, cheese, sour cream and other fermented milk. This article explains the exploration, functional properties and application of exopolysaccharide-producing LAB in fermented milk products. Keywords: LAB, Exopolysaccharides, and Fermented Milk.